Use of blends of gasoline with biomass pyrolysis-oil derived fractions as fuels in an Otto engine - Peláez Samaniego, Manuel Raúl (2011)
The aim of this paper is to report the results on the behavior of an Otto engine working with mixed gasoline with a fraction rich in carboxylic acid esters derived from biomass pyrolysis bio-oil, for the present it is called as "Bioflex". Sugarcane trash undergoes a fast pyrolysis process in PPR-200 pilot plant to produce Unicamp (Brazil) bio-oil. The process of separation of carboxylic acids from bio-oil, the production of esters of these acids, the process of mixing these esters with gasoline as well as the results of using this mixture in an Otto engine capacity 4 kW - component of a 2kW and generator - are described. Test tests determined that it is possible to mix up to 14 vol.% In Bioflex with type C gasoline used in Brazil. Engine performance with this mixture as compared to engine performance working with pure gasoline resulted in identical output power and fuel consumption. The results showed that it is technically feasible to use mixtures of carboxylic acid esters derived from biomass pyrolysis bio-oil with gasoline in conventional Otto engines.